PELATIHAN FRONT END WEB DEVELOPER di SMK BINTANG NUSANTARA - Jupron; Rahayu, Santi; Bahrein, Muhammad (Abdi Jurnal Publikasi, 2024)
SMK Bintang Nusantara, which is more familiarly called SMK Binusa, with educational services on software engineering has no Web Developer training for beginners. With that, this community service activity was held with front end web Developer training. The time for this training will be held on Friday, October 27, 2023 with 30 students. Training is carried out in the classroom. The resource person presented the material with a projector tool. The other committee as instructors who guide the participants in practicing the material presented by the resource persons. The implementation method is with the arrangement of preparatory activities, distributing consumption, opening the event, remarks, handing over mementos, material presentation, question and answer, door prize distribution, group photos and closing the event. This training motivates students in Front End Web Developer training to be sustainable.